Curcumin, demethoxycurcumin, bisdemethoxycurcumin, tetrahydrocurcumin and turmerones differentially regulate anti-inflammatory and anti-proliferative responses through a ROS-independent mechanism - Santosh K. Sandur (2018)
Curcumin, a component of turmeric (Curcuma longa), has been shown to exhibit chemopreventive activity. Whether analogs of curcumin (Cur), such as demethoxycurcumin (DMC), bisdemethoxycurcumin (BDMC), tetrahydrocurcumin (THC) and turmerones, modulate inflammatory signaling and cell proliferation signaling to same extent as curcumin was investigated. The results indicate that the relative potency for suppression of tumor necrosis factor (TNF)-induced nuclear factor-κB (NF-κB) activation was Cur > DMC > BDMC; thus suggesting the critical role of methoxy groups on the phenyl ring. THC, which lacks the conjugated bonds in the central seven-carbon chain, was completely inactive for suppression of the transcription factor. Turmerones also failed to inhibit TNF-induced NF-κB activation. The suppression of NF-κB activity correlated with inhibition of NF-κB reporter activity and with down-regulation of cyclooxygenase-2, cyclin D1 and vascular endothelial growth factor, all regulated by NF-κB. In contrast to NF-κB activity, the suppression of proliferation of various tumor cell lines by Cur, DMC and BDMC was found to be comparable; indicating the methoxy groups play minimum role in the growth-modulatory effects of curcumin. THC and turmerones were also found to be active in suppression of cell growth but to a much lesser extent than curcumin, DMC and BDMC. Whether suppression of NF-κB or cell proliferation, no relationship of any of the curcuminoid was found with reactive oxygen species (ROS) production. Overall, our results demonstrated that different analogs of curcumin present in turmeric exhibit variable anti-inflammatory and anti-proliferative activities, which do not correlate with their ability to modulate the ROS status. © The Author 2007. Published by Oxford University Press. All rights reserved.